COVID-19: The Case of Three Patients with the Same Diagnosis but Different Clinical and Laboratory Features. (25th May 2020) - Atere, Muhammed; Singh, Sukhdev; Arora, Krisha; Khan, Zohaib; Muzangwa, Lloyd; Bhavsar, Urvi; Nfonoyim, Jay M.
Abstract : SARS-CoV-2 is an RNA virus that causes COVID-19, which has been responsible for the pandemic that was declared in early 2020. Its pathological effect is majorly in the respiratory tract, but its full pathogenicity remains a mystery. Symptoms associated with COVID-19 include fever, cough, and shortness of breath. Some patients develop other symptoms like diarrhea. However, it is possible for other organs to be affected including the central nervous system, liver, and blood cells. The purpose of this case series is to unravel other factors associated with this disease, so we report three cases of COVID-19 that were hospitalized during the pandemic.